Methylene Blue as a Sensitizing Dye: Enhancement of the Photocatalytic Performance of a Peroxide-Functionalized Iron Molybdate by the Antenna Effect - José Balena G. Filho; Clóvis G. Vieira; Daniel B. de Jesus; Henrique F. V. Victória; Edmar A. Soares; Klaus Krambrock; Márcio César Pereira; Luiz Carlos A. Oliveira (Colorants, 2025)
The use of dyes as sensitizing agents to increase semiconductor activity is a strategy already adopted in the field of heterogeneous photocatalysis, but the compounds applied are noble metal-based and sometimes difficult to synthesize, which make it more expensive. In this work, it was discovered that methylene blue can perform such an effect on an iron molybdate functionalized with peroxo groups on the surface. This material, called MoOxoFe, was tested together with its analogue MoFe (produced without H2O2 in the synthesis) in the degradation of methylene blue. The rapid degradation of the dye led to the hypothesis of sensitization, which was investigated and proven by additional photocatalytic tests with sensitized material, MoOxoFe-MB, and spectroscopies, such as EPR and XPS.